“Love me with all your heart…and your mind.” : resilience resources of dementia caregivers in Singapore - Ng, Kristal Shi-En (Nanyang Technological University, 2021)
Background: Although literature concerning the longevity of dementia caregiving is extensive, the focus appears to be on the burdens of caregiving and how to mitigate them. In response, this paper aims to investigate the ways that resilience manifests in Singaporean caregivers of people with dementia, in particular, depicting the idiosyncratic experiences and factors that enhance resilience in their lives. Method: This study used qualitative thematic analysis to explore the resilience resources that dementia caregivers in Singapore adopted in their caregiving. Qualitative data from group sharing sessions was drawn from the larger Mindful Compassion Art Therapy for Dementia Caregivers (MCAT-DC) study (N = 10). Caregivers’ mean age was 57.8 and the average number of years spent caregiving was 4.8 years. Results: Seven themes emerged depicting the psychological and behavioural resources individual dementia caregivers employed to remain resilient in the face of caregiving: Compassionate Honor, Fulfilling Responsibility, Self-care as Other-care, Observing Gratitude, Seeking Sanctuary, Restructuring Care Routines and External Assistance. Conclusion: In summary, conviction in one’s motivation behind caregiving, strategies to maintain a positive outlook and practical changes to one’s lifestyle to accommodate the dementia symptoms are key components to promote resilience in dementia caregivers. These findings have relevance for governments and community organisations to develop strategies which enhance resilience in dementia caregivers in Singapore.